Study of the antioxidant potential of oat drinks enriched with plant components - N. V. Kupaeva; M. A. Ilina; M. V. Svetlichnaya; Yu. N. Zubarev (Пищевые системы)
Oxidative stress, to which many modern people are subjected, promotes the development of neurodegenerative, cardiovascular, inflammatory, oncological and other socially important diseases. The antioxidant system consisting in the endogenous and exogenous antioxidants exists in the body to regulate the action of free radicals and reactive oxygen species. The main source of exogenous antioxidants is food and this conditions an increase in the demand for functional foods. The market of functional drinks based on teas, cereal products, fruit and vegetable juices is developing especially actively. Drinks based on oat flakes with addition of plant components are distinguished by the high nutrition value being a rich source of dietary fibers, vitamins, minerals and antioxidants. During the experiment, a functional drink based on oat flakes and enriched with bananas, blueberry berries and a powder of elder (Sambucus nigra L.) berries recognized for the high content of anthocyanins was developed. The antioxidant potential of the experimental product was assessed by measuring the total antioxidant capacity (TAC) by the FRAP method and determining the antiradical activity (ARA) by the DPPH method. The TAC values for the aqueous and methanol extracts were 807.3±18.0 µmol quercitin equivalents /L and 948.7±47.9 µmol quercitin equivalents/L, respectively, which significantly exceeded the similar values in the control sample (by 2.44 and 1.69 times, respectively). The ARA of the methanol extract of the experimental drink was 86.49±2.01%, which was 1.9 times higher than the ARA of the control sample. It was established that about 10% of fat-soluble antioxidants are lost upon preparation of oat-based functional drinks with addition of elder berries.